Pushing the limits disabled dykes produce culture - Tremain, Shelley (Women's Press, 2009)
Cet impressionnant recueil de prose, de poésie, de chansons et d'art visuel rédigé par des lesbiennes handicapées est la première de deux anthologies liées (la seconde est un recueil d'essais). Dans son introduction percutante (« Nous sommes ici. Nous sommes handicapés et queer. Habituez-vous-y »), la rédactrice en chef Shelley Tremain appelle à la reconnaissance et à la compréhension du monde selon les lesbiennes handicapées. La collection elle-même est colérique, compatissante, drôle et surtout émouvante. Sherree Clark présente des extraits de son recueil de poésie et d'art Living with Arthritis. Margot K. Lane célèbre la sexualité dans un merveilleux poème intitulé « Full day ». Le récit posthume de Kathleen Martindale sur le cancer du sein est un appel à l’action contre le personnel médical insensible, tout comme la chronique de Kathleen Rockhill sur sa guérison d’un accident de voiture dévastateur. Combinant colère et célébration, Pushing the Limits est une révélation.
Keywords: amériques; anthologie; approches et analyses; arts; canada; capacitisme; corps; lesbianisme; littérature; outils; ouvrages de références; patriarcat; personnes lesbiennes; poésie; queer; racisme; ressource en ligne; régions géographiques; santé; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

Black atlantic, queer Atlantic: Queer imaginings of the middle passage - Tinsley, Omise'eke Natasha (GLQ: A Journal of Lesbian and Gay Studies, 2008)
Qu'est-ce que cela signifierait pour les études queer et sur la diaspora africaine de théoriser que l'Atlantique noir a toujours été un Atlantique queer ? Quelle nouvelle géographie – ou mieux, océanographie – des identités sexuelles, genrées, transnationales et raciales pourrait émerger d'une lecture queer des dislocations transocéaniques entre l'Afrique et la Caraïbe ? Cet article examine la diaspora africaine canonique et les textes théoriques queer en dialogue avec des textes créatifs récemment publiés qui imaginent les relations queer entre les kidnappés africains dans les cales des navires négriers. Ces textes créatifs, selon moi, théorisent plus largement l'espace conceptuel à la fois pour repenser les histoires sexuelles et raciales submergées et pour commenter les intersections entre la diaspora africaine et les expériences queer à une époque contemporaine de réfugiés haïtiens, de travailleurs dominicains transnationaux, et des militants « homosexuels » antillais internationaux. Les textes examinés comprennent celui de Paul GilroyBlack Atlantic (1993), Gender Trouble de Judith Butler (1990), Erzulie's Skirt d'Ana-Maurine Lara (2006) et Map to the Door of No Return de Dionne Brand (2001).
Keywords: afrique; amériques; approches et analyses; caraïbes; cours; discours dominant; fem3300; genre; identités LGBTQIA2+; premier cycle; queer; racisme; ressource en ligne; régions géographiques; sexualité; systèmes d'oppressions; thématiques

Transcultural bodies: female genital cutting in global context - Hernlund, Ylva; Shell-Duncan, Bettina (Rutgers University Press, 2007)
Female "circumcision" or, more precisely, female genital cutting (FGC), remains an important cultural practice in many African countries, often serving as a coming-of-age ritual. It is also a practice that has generated international dispute and continues to be at the center of debates over women's rights, the limits of cultural pluralism, the balance of power between local cultures, international human rights, and feminist activism. In our increasingly globalized world, these practices have also begun immigrating to other nations, where transnational complexities vex debates about how to resolve the issue. Bringing together thirteen essays,Transcultural Bodiesprovides an ethnographically rich exploration of FGC among African diasporas in the United Kingdom, Europe, and Australia. Contributors analyze changes in ideologies of gender and sexuality in immigrant communities, the frequent marginalization of African women's voices in debates over FGC, and controversies over legislation restricting the practice in immigrant populations.
Keywords: afrique; anthropologie; approches et analyses; australie; corps; cours; discipline; europe; histoire et politique; océanie; premier cycle; racisme; ressource en ligne; royaume-uni; régions géographiques; santé; sciences humaines; sex2283; sexisme; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; transculturalisme; violences

La sexualité entre sexisme et racisme: les descendantes de migrant·e·s du Maghreb et la virginité - Hamel, Christelle (Nouvelles Questions Féministes, 2006)
L'article présente le résultat d'une recherche sur la vie affective et sexuelle des jeunes Français-es descendant de migrant-e-s originaires du Maghreb, qui décrit comment les jeunes femmes se positionnent par rapport au principe de virginité. Alors que cette norme est un mode de contrôle de la sexualité des femmes, certaines le revendiquent, tandis que celles qui l'ont transgressé expriment combien cette décision leur fut difficile. Pour comprendre la prégnance de leur attachement à la valeur de la virginité, l'autrice replace leurs discours et pratiques dans le contexte social qui les a fait naître. Elle décrit donc comment les discriminations et la stigmatisation racistes façonnent l'expérience de vie de ces jeunes femmes et montre combien cette expérience du racisme se combine à l'expérience du sexisme dans les familles et dans la société globale. Ici, l'imbrication du sexisme et du racisme fait peser sur elles un système de contraintes complexe qui les soumet à des injonctions paradoxales. Ce n'est qu'au regard de ces injonctions que la revendication par certaines de cette norme qui par ailleurs les opprime devient intelligible.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; afrique; approches et analyses; corps; cours; discipline; europe; france; histoire et politique; intersectionnalité; maghreb; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; virginité; études démographiques

Prostitution et immigration des femmes latino-américaines en Espagne - Oso Casas, Laura (Cahiers du Genre, 2006)
L’objectif de cet article est de montrer qu’une bonne partie des femmes latino-américaines, contrairement à l’image souvent mise en avant de la femme objet de trafic, ont pris la décision de migrer en étant conscientes de l’activité qu’elles allaient pratiquer en Espagne. Cependant, bien qu’elles puissent opter volontairement pour le « travail » sexuel, devenant les principales pourvoyeuses économiques des foyers transnationaux (actrices de la migration, actrices économiques et du développement), elles sont prises dans plusieurs circuits qui contribuent à la reproduction des inégalités sociales. Ces circuits sont sous-tendus par l’articulation de plusieurs facteurs : la circulation des personnes, la mobilité des prostituées, la pression du foyer transnational, l’irrégularité juridique, ainsi que l’inégalité de genre.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique centrale; amérique du sud; amériques; approches et analyses; cours; discipline; espagne; europe; immigration; inégalités; migration; postmodernisme; premier cycle; prostitution; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc1061; sociologie; système colonial; systèmes d'oppressions; thématiques; travail

A new Vision for advancing our movement for reproductive health, reproductive rights and reproductive justice - Asian Communities for Reproductive Justice (Asian Communities for Reproductive Justice, 2005)
Forward Together’s (then Asian Communities for Reproductive Justice or ACRJ) groundbreaking analysis of the framework and vision for reproductive justice, described by organizations and funders as revelatory and pivotal to the field.
Keywords: amériques; approches et analyses; asie; droits des femmes*; femmes* asiatiques; femmes* de couleur; inégalités; justice reproductive; justice sociale; militance; racisme; ressource en ligne; régions géographiques; santé; santé reproductive; sexisme; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle; états-unis

Histoires d’objets - Fassa, Farinaz; Kraus, Cynthia; Malbois, Fabienne (Nouvelles Questions Feministes, 2005)
Number: 1 Publisher: Éditions Antipodes
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; corps; cours; discipline; europe; france; féminisme radical; patriarcat; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Black sexual politics: African Americans, gender, and the new racism - Hill Collins, Patricia (Routledge, 2005)
To a large extent, scholarship on black politics often focuses primarily on institutions, rule of law, processes, political actors, and citizens but with very little attention to issues of gender and sexuality. In contrast, the principal aim of this book is to explore what the author sees as the inextricable links between racism and gender. The basic thesis of this well-written, important, and provocative book is that the fight against racism, especially the “new racism,” can never be won without first challenging sexism, which simultaneously oppresses African-American men and women.
Section: ix, 374 p. ; 23 cm
Keywords: afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; féminismes noirs; intersectionnalité; premier cycle; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sex2283; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; théorie critique de la race; violences; états-unis

The Black studies reader - Bobo, Jacqueline; Hudley, Cynthia; Michel, Claudine (Routledge, 2004)
Black studies emerged from the tumultuous social and civil rights movements of the 1960s and empowered African Americans to look at themselves in new ways and pass on a dignified version of Black history. However, it also enriched traditional disciplines in profound and significant ways. Proponents of Black and ethnic studies confronted the false notion that scholarly investigations were objective and unbiased explorations of the range of human knowledge, history, creativity, artistry, and scientific discovery. As they protested against hegemonic notions like universal psychology and re-evaluated canonical texts in literature, a new model of academic inquiry evolved: one committed to serving a range of populations, that critiqued traditional politics, culture, and social affairs, and worked with activist energy for the transformation of the existing social order. With an all-star cast of contributors, The Black Studies Reader takes on the history and future of this multi-faceted academic field. Topics include Black feminism, cultural politics, Black activism, lesbian and gay issues, African American literature and film, education, and religion. This authoritative collection takes a critical look at the current state of Black studies and speculates on where it may go from here.
Keywords: LGBTQIA2+; afro-féminisme; amériques; approches et analyses; féminisme islamique; histoire et politique; identités LGBTQIA2+; militance; outils; ouvrages de références; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppressions; thématiques; états-unis

Aberrations in Black: Toward a queer of color critique - Ferguson, Roderick A. (University of Minnesota Press, 2004)
A hard-hitting look at the regulation of sexual difference and its role in circumscribing African American culture. The sociology of race relations in America typically describes an intersection of poverty, race, and economic discrimination. But what is missing from the picture—sexual difference—can be as instructive as what is present. In this ambitious work, Roderick A. Ferguson reveals how the discourses of sexuality are used to articulate theories of racial difference in the field of sociology.
Keywords: amériques; approches et analyses; cours; discipline; discours dominant; fem1000; fem3300; histoire et politique; hétérosexisme; identités LGBTQIA2+; premier cycle; queer; queer of color; racisme; ressource en ligne; régions géographiques; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

Queer globalizations: citizenship and the afterlife of colonialism - Cruz, Arnaldo; Manalansan, Martin F. (New York University Press, 2002)
Globalization has a taste for queer cultures. Whether in advertising, film, performance art, the internet, or in the political discourses of human rights in emerging democracies, queerness sells and the transnational circulation of peoples, identities and social movements that we call "globalization" can be liberating to the extent that it incorporates queer lives and cultures. From this perspective, globalization is seen as allowing the emergence of queer identities and cultures on a global scale. The essays in Queer Globalizations bring together scholars of postcolonial and lesbian and gay studies in order to examine from multiple perspectives the narratives that have sought to define globalization. In examining the tales that have been spun about globalization, these scholars have tried not only to assess the validity of the claims made for globalization, they have also attempted to identify the tactics and rhetorical strategies through which these claims and through which global circulation are constructed and operate.
Section: vii, 274 p. ; 24 cm.
Keywords: 1900-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; racisme; régions géographiques; sexualité; shm4000; système colonial; systèmes d'oppressions; thématiques; états-unis

Re-orienting desire: The gay international and the arab world - Massad, Joseph (Public Culture, 2002)
Keywords: approches et analyses; cours; discours dominant; fem3400; identités LGBTQIA2+; islam; premier cycle; racisme; ressource en ligne; sexualité; système colonial; systèmes d'oppressions; thématiques; violences

Lesbian empire: Radical crosswriting in the Twenties - Wachman, Gay (Rutgers University Press, 2001)
Gay Wachman provides a critical new reading of sexually radical fiction by British women in the years during and after the First World War. She contrasts works by Sylvia Townsend Warner, Virginia Woolf, Rose Allatini, and Evadne Price with more politically and narratively conservative novels by Radclyffe Hall and Clemence Dane. These writers, she states, formed part of an alternative modernist tradition that functioned both within and against the repressive ideology of the British Empire, using fantasy as a means of reshaping and critiquing a world fragmented by war. Wachman places at the center of this tradition Sylvia Townsend Warner's achievement in undermining the inhibitions that faced women writing about forbidden love. She discusses Warner's use of crosswriting to transpose the otherwise unrepresentable lives of invisible lesbians into narratives about gay men, destabilizing the borders of race, class, and gender and challenging the codes of expression on which imperialist patriarchy and capitalism depended.
Keywords: amour interdit; approches et analyses; arts; discipline; europe; littérature; patriarcat; personnes lesbiennes; racisme; royaume-uni; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; transgression; études littéraires